2008
DOI: 10.1007/s00380-007-1008-7
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of amlodipine and atorvastatin on blood pressure, left ventricular remodeling, and C-reactive protein in hypertensive patients with primary hypercholesterolemia

Abstract: Our aim in this study was to investigate the changes of serum high-sensitive C-reactive protein (hs-CRP) and uric acid (UA), and evaluate the synergistic effect of amlodipine and atorvastatin on blood pressure and left ventricular remodeling in hypertensive patients with primary hypercholesterolemia. One hundred and twenty-six hypertensive patients with hypercholesterolemia were randomized into amlodipine group (10 mg/day, group A, n = 65) and amlodipine (10 mg/day) plus atorvastatin group (20 mg/day, group B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…13) In vivo studies revealed that atorvastatin inhibited LV remodeling in spontaneously hypertensive rats (SHRs) through the induction of cardiomyocyte apoptosis; up-regulation of myocardial P27 protein expression; down-regulation of PKD/MEF2D activation; and decreasing blood pressure, serum uric acid concentration, and myocardial angiotensin II concentration. 6,[14][15][16] The effects of atorvastatin on myocardial CTGF expression in SHRs are not clear. SHRs develop high blood pressure and LV hypertrophy at an early age, and are a commonly used model of essential hypertension in humans.…”
Section: H Ypertension That Results In Left Ventricular (Lv) Hyper-mentioning
confidence: 99%
See 1 more Smart Citation
“…13) In vivo studies revealed that atorvastatin inhibited LV remodeling in spontaneously hypertensive rats (SHRs) through the induction of cardiomyocyte apoptosis; up-regulation of myocardial P27 protein expression; down-regulation of PKD/MEF2D activation; and decreasing blood pressure, serum uric acid concentration, and myocardial angiotensin II concentration. 6,[14][15][16] The effects of atorvastatin on myocardial CTGF expression in SHRs are not clear. SHRs develop high blood pressure and LV hypertrophy at an early age, and are a commonly used model of essential hypertension in humans.…”
Section: H Ypertension That Results In Left Ventricular (Lv) Hyper-mentioning
confidence: 99%
“…The apoptosis rate in myocardiocytes in the SHR-DW group was reduced, whereas 12-week treatment with atorvastatin induced myocardiocyte apoptosis accompanied by alleviated LV remodeling. This indicated that in SHRs aged [8][9][10][11][12][13][14][15][16][17][18][19][20] weeks, reduced apoptosis in myocardiocytes was involved in the development of LV remodeling, and that the effects of atorvastatin on apoptosis may be applicable only to SHRs of this age. Studies on myocardiocyte apoptosis and the effects of atorvastatin on this parameter in SHRs older than 20 weeks should be carried out.…”
mentioning
confidence: 99%
“…First, we selected subjects never treated with antihypertensive drugs or statins, in order to avoid the possible influence of these treatments LV characteristics and metabolic profile. [31][32][33][34] Second, we matched the 4 groups by age, sex and BMI, all factors known to influence LV characteristics; moreover, we matched HIV þ and HIVÀ subjects also by smoking habit, since smoking …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of coronary artery disease (CAD) is occurring much more frequently. Cardiovascular disease is characterized by a complex multifactorial pathophysiology, 1 which involves extracellular matrix (ECM) degradation and vascular wall remodeling. Positive arterial remodeling (compensatory enlargement) is more often observed in lesions of patients who have acute coronary syndromes (ACS) or vulnerable (rupture-prone) plaques.…”
Section: Introductionmentioning
confidence: 99%